"Behind Every Great Man…": The Male Marriage Wage Premium Examined Qualitatively. Issue 1 (February 2014) - Ashwin, Sarah; Isupova, Olga
<x xml:space="preserve">Abstract</x> Studies across diverse national contexts reliably show that married men earn more than unmarried men, but the mechanisms responsible for this are still disputed. This article explores the male marriage wage premium from a new perspective, using longitudinal qualitative data from Russia (N = 94). Qualitative research is particularly suited to identifying underlying processes and, by analyzing men's accounts of the influence of their marital trajectories on their work, the authors were able to reexamine existing hypotheses and develop new ones. They propose 4 mechanisms that they hypothesize can influence men's work motivation and performance: premarital planning, 2 distinct "breadwinner" effects using expectancy and self determination theory, and monitoring by wives. They integrate these mechanisms within gender theory, arguing that the treatment aspect of the male marriage wage premium is an outcome of the "coproduction" of masculinity within marriage. Their recontextualization of existing theory also enables them to reveal weaknesses in the specialization hypothesis.